K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 12 2021

\(\left(3x^2-2x+3\right):\left(x^2+1\right)\\ =\left[3\left(x^2+1\right)-2x\right]:\left(x^2+1\right)\\ =3\left(\text{dư }-2x\right)\\ \left(3x^2-4x+4\right):\left(x^2+2\right)\\ =\left(3x^2+6-4x-2\right):\left(x^2+2\right)\\ =\left[3\left(x^2+2\right)-4x-2\right]:\left(x^2+2\right)\\ =3\left(\text{dư }-4x-2\right)\)

29 tháng 9 2017

bài 1

x2-2x-3

=x2+x-3x-3

=x(x+1)-3(x+1)

=(x-3)(x+1)

29 tháng 9 2017

bài 2

b) x2(x2+1)-x2-1=0

=>x2(x2+1)-(x2+1)=0

=>(x2+1)(x2-1)=0

=>x2+1=0 hoặc x2-1=0

=>x2=-1 (loại)hoặc x2=1

=>x=\(\pm\) 1

vậy x=\(\pm\)1

16 tháng 6 2017

3x-2x +4